2018
DOI: 10.1007/s11244-018-0939-9
|View full text |Cite
|
Sign up to set email alerts
|

Volta Potential Evolution of Intermetallics in Aluminum Alloy Microstructure Under Thin Aqueous Adlayers: A combined DFT and Experimental Study

Abstract: In this work, first-principle density functional theory (DFT) was used to calculate the work function and Volta potential differences between aluminum alloy matrix and two intermetallic phases (Mg 2 Si and Al 2 Cu) with varying surface terminations as a function of adhering monolayers (ML) of water. The calculated data were compared with experimental local Volta potential data obtained by the scanning Kelvin probe force microscopy (SKPFM) on a commercial aluminum alloy AA6063-T5 in atmospheric environments wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 77 publications
3
54
0
Order By: Relevance
“…The naturally formed passive film over the ferrite is different than that of the austenite, giving rise to a typical Volta potential difference of 40-70 mV of numerous DSS's. 12,13,19,25 Laurent et al 24 reported a chromium-rich oxide, in the form of chromia, that became further enriched in the passive film upon passivation in nitric acid, with the thickness, however, not been majorly altered. This may explain the reason why the Volta potential of ferrite and austenite of the DSS were similar after immersion in nitric acid.…”
Section: Effect Of Nitric Acid Oxidation On the Passive Filmmentioning
confidence: 99%
See 3 more Smart Citations
“…The naturally formed passive film over the ferrite is different than that of the austenite, giving rise to a typical Volta potential difference of 40-70 mV of numerous DSS's. 12,13,19,25 Laurent et al 24 reported a chromium-rich oxide, in the form of chromia, that became further enriched in the passive film upon passivation in nitric acid, with the thickness, however, not been majorly altered. This may explain the reason why the Volta potential of ferrite and austenite of the DSS were similar after immersion in nitric acid.…”
Section: Effect Of Nitric Acid Oxidation On the Passive Filmmentioning
confidence: 99%
“…Scanning Kelvin probe force microscopy (SKPFM), instead, is one technique that can provide electronic information in nanometre scale which in turn provide insightful information into electrochemical processes, being helpful in assessing the likelihood of local corrosion events such as micro-galvanic corrosion of multi-phase alloys. [10][11][12][13] It measures the Volta potential with a sensitivity of 1 mV and a spatial resolution of~15 nm. 12,13 The Volta potential is an intrinsic property of a metal and forms with the surface potential the Galvani potential, which describes the real electrode potential of the metal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Employed under either ambient, inert, or electrolytic environments, SKPFM can spatially resolve features at the nanoscale, [3][4][5] and has there fore found use in a wide range of diverse applications, including semiconductor [4][5][6][7] and electrical device characterization, [8][9][10][11][12] as well as corrosion studies. [13][14][15][16][17][18][19][20] SKPFM produces nanoscale maps of Volta potential differ ences (VPD or ψ), which can be calculated theoretically from the difference in work function between the sample surface and the probe (which acts as a pseudo reference), as shown below in 3, [21][22][23] Equation 1.…”
mentioning
confidence: 99%